Laparoscopic partial nephrectomy for renal cell carcinoma in a horseshoe kidney - Benidir, Tarik; Coelho de Castilho, Tiago Jacometo; Lobo Cherubini, Guilherme Rodrigo; de Almeida Luz, Murilo (Canadian Urological Association Journal, 2014)
Horseshoe kidney has an incidence rate ranging from 1 in 400 to 1 in 1000, with a 2:1 ratio in men. It also has a predilection for chromosomal aneuploidies. From a pathophysiology standpoint, this anomaly occurs during the second to sixth week of gestation when the inferior portion of the metanephric blastema fuses to form an isthmus, commonly in the lower renal pole (90%). As a result of this fusion, the kidney may not bypass the inferior mesenteric artery and is impeded in its ascent. With an aberrant anatomical orientation and location, complications arise including hydronephrosis, renal calculi and a twofold risk of Wilms tumour. Despite these findings, the association of renal cell carcinoma (RCC) within a horseshoe kidney is extremely rare and fewer than 200 cases have been described. Therapeutically speaking, partial nephrectomies are the gold standard of treatment for renal tumours smaller than 4 cm in diameter, with a growing indication to accomplish this procedure by laparoscopic or robotic means. We report a case of an asymptomatic 58-year-old male with an incidental computed tomography scan finding of a 4-cm solid mass in the right moiety of a horseshoe kidney. He was treated by laparoscopic partial nephrectomy. There have only been 2 other reported cases to our knowledge on a laparoscopic partial nephrectomy in a horseshoe kidney for RCC. We believe that, in experienced hands, the laparoscopic approach may be used successfully for this clinical situation.